PENGARUH PENGGUNAAN METODE CANTOL ROUDHOH TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5 - 6 TAHUN DI PAUD LILIK KECAMATAN BUKITRAYA PEKANBARU - Indah Putri Ramadhan; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aim to know the effect of the use cantol raudhoh method of the reading skills of children ages 4-5 years old at PAUD LILIK distrik Bukitraya at ages 5 until 6 years old that consist of 21 student, namly research sample of children aged 5 until 6 class B that consis 21 children, taken using test formula T. The method used is pre-eksperiment design seen as an eksperiment not actual and the research uses a moder or one group per-test-postest design.The technique of collecting data used method of observation sheet assessment sheet and method of documentation. The technique analyzing data used with statistic technique t-test by using SPSS for windows ver 20.0Based on test resul obtained hipothese are that the lowed value and upper value is negative it can be concluded that Ha be accepted and Ho rejected. The result tcount = 9.181 and ttable df from 20 at the level of errors 0,05 so that ttable = 2,080, there for a significant influence on the ability to read the beginning of children ages 5 to 6 years after using cantol roudhoh method. The research aim to know the effect of the use cantol raudhoh method of the reading skills of children ages 4-5 years old at PAUD LILIK distrik Bukitraya , Pekanbaru thus a significant influence on the ability to read the beginning of children aged 5 to 6 years after using a media cantol roudhoh.Keywords: the research, cantol roudhoh, reading, young learners